Infiltrating pattern and prognostic value of tertiary lymphoid structures in resected non-functional pancreatic neuroendocrine tumors. Issue 2 (14th October 2020) - Zhang, Wu-Hu; Wang, Wen-Quan; Han, Xuan; Gao, He-Li; Xu, Shuai-Shuai; Li, Shuo; Li, Tian-Jiao; Xu, Hua-Xiang; Li, Hao; Ye, Long-Yun; Lin, Xuan; Wu, Chun-Tao; et al.
Abstract : Background: Tertiary lymphoid structures (TLS) are associated with favorable survival and play a critical role in most solid tumors. However, investigations of TLS are lacking in patients with grade 1 or grade 2 (G1/G2) non-functional pancreatic neuroendocrine tumors (NF-PanNETs). This study aimed to investigate the presence, cellular composition, association with tumor-infiltrating immune cells, and prognostic value of TLS in G1/G2 NF-PanNETs. Methods: Tumor tissues from a 182-patient Fudan cohort and a 125-patient external validation set were assessed by H&E staining, immunohistochemistry, and/or multispectral fluorescent immunohistochemistry. Results: TLS were identified in more than one-third of patients with G1/G2 NF-PanNETs and were located peritumorally, either just outside the tumor tissue or in the stromal area. TLS were mainly composed of B-cell follicles with germinal centers and T-cell zones with dendritic cells. Kaplan-Meier analyses showed that the presence of TLS correlated with both longer recurrence-free survival (RFS, p<0.001) and overall survival (OS, p=0.001), but the number of TLS had no prognostic significance. Multivariate Cox-regression analyses demonstrated that the presence of TLS, WHO classification, and 8th edition American Joint Committee on Cancer (AJCC 8th ) tumor-node-metastasis (TNM) stage were independent prognostic factors for RFS (p=0.004, p=0.001, and p<0.001, respectively) and OS (p=0.009, p=0.008, and p=0.019, respectively). These results were confirmed using an external validation set. Finally, a nomogram incorporating the presence of TLS was constructed to predict the probability of 5-year RFS of resected G1/G2 NF-PanNETs, which improved on the current WHO classification and AJCC 8th TNM stage. Conclusions: The presence of TLS is an independent and favorable predictor of resected G1/G2 NF-PanNETs, which may play a role in cancer immunobiology.